Best One-Sided Multiplier Approximation by Operators - K. Al-Saidy, Saheb; J. Al-Jawari, Naseif; F. Hassan, Raad (Al-Nahrain Journal of Science, 2023)
The aim of studying this research is to find the best one-sided multiplier approximation of unbounded function in space,  by using type of operators  by means of operators of algebraic polynomials as well as to show the relationship between the multiplier averaged modules of smoothness (-modules) and variation of unbounded functions in space.